Desain Benzene Distiller Pada Prarancangan Pabrik Benzene, Toluene, Dan Xylene Menggunakan Proses Cyclar Bp/Uop - Elisa Pebrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Benzene, toluene, and xylene (BTX) are petrochemical materials that are produced through a catalytic reforming process from naphtha. Benzene and toluene are among the products that are widely used for chemical raw materials, one of which is toluene which is used as a solvent and intermediate in the manufacturing process of high octane chemicals and gasoline components, while the demand for xylene has increased along with the increasing demand for polyester fibers and films. This factory is designed with a production capacity of 602.606 tons/year. One of the main equipment in this factory is a benzene distiller. This apparatus is designed to separate benzene from toluene, xylene, pentane, pentylene, hexane, hexylene, octylene, octane and heptylene. This benzene distiller is a sieve tray type distillation tower. This benzene distiller is operated at a temperature of 64,77°C and a pressure of 1,01 bar. The distillate flow rate of 12036356,37 lb/hr consists of pentylene, pentane, hexylene, hexane, and benzene and the bottom flow rate is 843889,17 lb/hr consisting of octylene, octane, hexylene, hexane, heptylene, xylene, and toluene as well as the flow rate of the benzene product was 48669,52 lb/hr. The height of the tower is 28,88 m and a diameter of 5,94 m with a torispherical type head and skirt as supports.Keywords: BTX, benzene distiller, catalityc reforming, sieve tray